2011
DOI: 10.1021/jp2016006
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking AMBER Force Fields for RNA: Comparisons to NMR Spectra for Single-Stranded r(GACC) Are Improved by Revised χ Torsions

Abstract: Accurately modeling unpaired regions of RNA is important for predicting structure, dynamics, and thermodynamics of folded RNA. Comparisons between NMR data and molecular dynamics simulations provide a test of force fields used for modeling. Here, NMR spectroscopy, including NOESY, 1H–31P HETCOR, DQF-COSY, and TOCSY, was used to determine conformational preferences for single-stranded GACC RNA. The spectra are consistent with a conformational ensemble containing major and minor A-form-like structures. In a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
253
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(276 citation statements)
references
References 71 publications
20
253
2
Order By: Relevance
“…These simulations show the UUCG loop conformation and dynamics on longer timescales and not only help to assess and validate the force field performance, but show that results obtained with the CPU and GPU versions of the PMEMD code behave similarly and also that similar results are seen with the specialized Anton supercomputer (Shaw Steinbrecher et al (2012). e Yildirim et al (2011). f Chen and García (2013).…”
Section: Instability In Standard MD Simulations Of the Uucg Tetraloopmentioning
confidence: 64%
See 3 more Smart Citations
“…These simulations show the UUCG loop conformation and dynamics on longer timescales and not only help to assess and validate the force field performance, but show that results obtained with the CPU and GPU versions of the PMEMD code behave similarly and also that similar results are seen with the specialized Anton supercomputer (Shaw Steinbrecher et al (2012). e Yildirim et al (2011). f Chen and García (2013).…”
Section: Instability In Standard MD Simulations Of the Uucg Tetraloopmentioning
confidence: 64%
“…However, Yildirim and colleagues also reported that they observed another non-Aform structure with significant population in their longer MD simulation. The results from our independent M-REMD simulations using these parameters (192 replicas, ∼1 µsec per replica) do in fact show that intercalated structures that are inconsistent with the NMR data are the main representatives of the ensemble, accounting for ∼40% of structures (including a conformation consistent with the non-A-form one reported by Yildirim et al 2011). While the overall populations of NMR major and NMR minor from the ff99 + χ Yil simulations do not reproduce the experimentally determined populations, the ratio of NMR major to NMR minor is roughly 2.5:1, which is consistent with the relative populations of these two structures from the experimental ensemble; we note that no other force field tested was able to do this.…”
Section: Instability In Standard MD Simulations Of the Uucg Tetraloopmentioning
confidence: 69%
See 2 more Smart Citations
“…Additionally, for a similar tetranucleotide (GACC) it was shown that intercalated structures would lead to peaks that would be easy to detect because they would appear in unique and uncrowded regions of the spectra. 57 Comparison of MD with NMR for the tetranucleotides is reported in figure 4. As it can be seen, the MaxEnt corrections improve the agreement with experimental scalar couplings for AAAA and CCCC with respect to both Amber and Amber αζ force fields.…”
Section: Validation On Rna Tetranucleotidesmentioning
confidence: 99%